Analisis Implementasi Teknologi Blockchain pada Sistem Informasi untuk Meningkatkan Keamanan Data Mahasiswa - Virki Fardian Nur Rohman; Muhammad Rahmadika (Pusat Riset dan Inovasi Nasional, 2025)
Given the increasing threats to personal data managed by educational institutions, student data security has become a critical issue in the digital era. This study aims to examine how the implementation of blockchain technology in academic information systems can enhance data security. The study employs literature review, qualitative analysis of case studies from universities that have implemented blockchain, and triangulation for data validation. The results indicate that using blockchain significantly improves data security. The security score increased from 4 before implementation to 9 after implementation. Compared to traditional methods, the decentralization and encryption of blockchain systems make data more resistant to manipulation and forgery. According to this study, there is a need for legislation to support the use of blockchain in education. Additionally, further research is required on the scalability and cost-effectiveness of this technology in higher education institutions.